CITIZEN JOURNALISM MELAWAN MAINSTREAM MEDIA - Yustitia, Senja (Jurnal The Messenger, 2010)
The importance of mass media tend to described as the fourth pillar of a nation, that represents democration, after the existence of nation sets of government forces. In line with teori agenda setting thesis emphasize media force to influence society agenda, and in the end will brought particular change towards. Post-reformation, media tend to isolate themselves from society needs although society is their biggest and the most loyal audiences. Thus called mainstream media consider economic importance as the most important aspect, this fact encouraging media to deviate from their main purpose as the provider of idea and knowledge, whether to give out information or to accomodate various needs and interest. This condition known as the end of media , related with this condition the emergence an alternate known as citizen journalism really needed to balance out information current. The existence of citizen journalism encourage audience to participate as subject and object to control journalistic mechanism.